Framing Pemberitaan Kebijakan dan Pernyataan Menkeu Purbaya Terhadap IHSG di Media Kontan.co.id Dan CNBC Indonesia - Laelatul Najma Maharani Azzahra; Diryo Suparto; Ike Desi Florina (PERSPEKTIF, 2026)
Media coverage of economic policy not only disseminates information but also constructs social reality that shapes public understanding of government policies. Differences in the editorial characteristics of economic news media may produce distinct framing of the same issue. This study aims to analyze and compare the framing of news coverage on the policies and statements of Minister of Finance Purbaya Yudhi Sadewa concerning the capital market in Kontan.co.id and CNBC Indonesia. The study employed a descriptive qualitative approach using Zhongdang Pan and Gerald M. Kosicki’s framing analysis model, which examines four analytical structures: syntactic, script, thematic, and rhetorical. The data consisted of four news articles purposively selected from 24 relevant articles published between September 8 and November 8, 2025. The findings indicate that Kontan.co.id framed the issue through an institutional-procedural perspective by emphasizing policy mechanisms, inter-institutional relations, and capital market governance. In contrast, CNBC Indonesia highlighted government action, market responses, and the protection of retail investors through more direct and accessible language. The study concludes that differences in the editorial characteristics of the two media influence the construction of economic reality, demonstrating that economic news media function not only as information providers but also as actors shaping public interpretations of government policy signals in the capital market.